Racial Politics in the Contemporary Prison Society: The Importance of Race and Ethnicity to Prison Social Organization - INFANTE, ARYNN A. (Criminal justice and behavior, 2023)
Prior research documents race and ethnicity as central to how individuals navigate the social and physical space of prisons. Racial segregation persists as a feature of prison life, and in navigating this racialized structure, racial groups construct and enforce a set of racialized norms to govern behavior (i.e., the “racial code”) that reinforce and reify prison racial politics. These processes, however, have remained largely descriptive in nature. Using data from a sample of incarcerated men in Arizona prisons (N = 251), this article extends prior work by operationalizing the concept of the racial code, assessing its dimensionality, distinguishing it from the prison code, and differentiating how features of prison social organization influence racial code adherence and mobilization. Results suggest that the racial code is distinct from the prison code and that racial differences exist in the extent of adhering to versus mobilizing the racial code, net of gang status.